2019
DOI: 10.1021/acs.jpcc.9b02667
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Microstructural Effects of Mo3+/Mo5+ Codoping on Properties and Photocatalytic Performance of Nanostructured TiO2 Thin Films

Abstract: Mo 3+ /Mo 5+ equally codoped TiO 2 thin films (0.050−0.100 mol % individually) were fabricated by spin coating on polished fused silica glass substrates followed by annealing at 450 °C for 2 h. The highly transparent (>80%) films consisted of poorly crystallized single-crystal anatase, where interstitial solid solubility decreases the lattice parameters, with a reversed trend at the highest codoping level arising from supersaturation and V O •• formation. The crystallinities correlate with the alternating tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…7,55 Intervalence charge transfer (IVCT), involving electron exchange between dopant and matrix ions or between codopant ions, and multivalence charge transfer (MVCT), involving electron exchange between multiple-dopant ions and matrix ions, both without defect formation otherwise, represent underappreciated means of explaining valence changes. [56][57][58][59][60][61][62][63][64][65][66][67][68][69] Three types of colour centres (F 0 , F + , F ++ ) have been suggested by modelling 70 and validated experimentally for pure CeO 2Àx . 71 While, the latter were generated at room temperature, high-energy irradiation often is required to create the Schottky pairs that are involved in the generation of such F-centres.…”
Section: Ce-o Defect Equilibriamentioning
confidence: 99%
“…7,55 Intervalence charge transfer (IVCT), involving electron exchange between dopant and matrix ions or between codopant ions, and multivalence charge transfer (MVCT), involving electron exchange between multiple-dopant ions and matrix ions, both without defect formation otherwise, represent underappreciated means of explaining valence changes. [56][57][58][59][60][61][62][63][64][65][66][67][68][69] Three types of colour centres (F 0 , F + , F ++ ) have been suggested by modelling 70 and validated experimentally for pure CeO 2Àx . 71 While, the latter were generated at room temperature, high-energy irradiation often is required to create the Schottky pairs that are involved in the generation of such F-centres.…”
Section: Ce-o Defect Equilibriamentioning
confidence: 99%
“…There are various methods for preparing perovskite oxide such as hydrothermal, microwave, precipitation, sol–gel, etc. 26 . The La Fe 0.7 Co 0.3 O 3 perovskite catalyst was prepared using the thermal sol–gel method.…”
Section: Methodsmentioning
confidence: 99%
“…Doping of TiO 2 with Mo triggered great interest, which aroused the radius of Mo 5+ (0.61 Å) and Mo 6+ (0.59 Å) and which are similar to that of Ti 4+ (0.605 Å). This means that Mo 5+ /Mo 6+ can effectively substitute Ti 4+ in its lattice structure with low lattice distortion [20]. Doping of TiO 2 with Mo cannot only influence the surface properties, but also affect the electronic and the optical properties and the material.…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic performance of the prepared materials was investigated for photocatalytic reduction of CO 2 to methane. Similarly, Esposito et al demonstrated the synthesis of Mo-doped TiO 2 via a reverse micelle solgel approach using titanium butoxide and ammonium heptamolybdate tetrahydrate as metals precursors, cyclohexane as an oil phase, and polyoxyethylene (20) oleyl ether and Brij O20 as surfactants [26]. Their results exhibited that at Mo concentrations ≥ 2.5%, all phases of TiO 2 coexist, i.e., anatase, rutile, and brookite.…”
Section: Introductionmentioning
confidence: 99%